Development of Cashew and Pistachio Ladders through a Food-Processing Approach - Nicki Shwe Yee; Hoi Ka Ng; Jingjing Zeng; Jinjing Bao; Dianne E. Campbell; Paul J. Turner; Nanju Alice Lee (Foods, 2024)
Following successful oral immunotherapy (OIT) for peanut allergy using boiled peanuts (BOPI trial), this study investigated the potential of wet-thermal-processing-induced allergen modification, specifically soaking and boiling (1–4 h) to reduce the allergenicity of cashew and pistachio allergens. In addition, this study provides a foundation of understanding for developing safer forms of cashew/pistachio administration for application in OIT by gradual exposure to increasing doses of modified allergens with reduced potency as an “allergen ladder”. An SDS-PAGE analysis and an intrinsic-fluorescence spectroscopy revealed altered tertiary structures of the allergens, leading to their denaturation and even degradation. Notably, the reduction in both allergen-specific polyclonal IgG and human-specific IgE (sIgE) binding correlated with the treatment time, with the most significant decrease observed after 4 h of boiling. In contrast, shorter soaking treatments showed negligible effects on the IgE-binding capacity of these nuts, therefore indicating a further need for optimization. These findings indicate that extended boiling effectively reduced the amounts of the highly potent allergenic component Ana o 3 in cashew and Pis v 1 in pistachio, as confirmed by ELISA using polyclonal anti-Ana o 3 antibodies, and an immunoblot showed decreased IgE epitope binding in cashew and pistachio allergens, which further modified their allergenic profiles. This approach shows promise as a viable method for offering a safer therapeutic option for cashew/pistachio allergy.